Sequential Double Polymer Click Reactions for the Preparation of Regular Graft Copolymers - Durmaz, Hakan; Dag, Aydan; DAĞ, AYDAN; Hızal, Gürkan; Tunca, Ümit (My University, 2011)
In this study, graft copolymers with regular graft points containing polystyrene (PS) backbone and poly(methyl methacrylate) (PMMA), poly(tert-butyl acrylate) (PtBA), or poly (ethylene glycol) (PEG) side chains were simply achieved by a sequential double polymer click reactions. The linear alpha-alkyne-omega-azide PS with an anthracene pendant unit per chain was produced via atom transfer radical polymerization of styrene initiated by anthracen-9-ylmethyl 2-((2-bromo-2-methylpropanoyloxy)methyl)-2-methyl-3-oxo-3-(prop-2-ynyloxy) propyl succinate. Subsequently, the azide-alkyne click coupling of this PS to create the linear multiblock PS chain with pendant anthracene sites per PS block, followed by Die Is-Alder click reaction with maleimide end-functionalized PMMA, PtBA, or PEG yielded final PS-g-PMMA, PS-g-PtBA or PS-g-PEG copolymers with regular grafts, respectively. Well-defined polymers were characterized by H-1 NMR, gel permeation chromatography (GPC) and triple detection GPC. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 1195-1200,2011